Beyond Anpanman the (Super)hero: Investigating Figures of Hero and Idol in BTS’s Songs - Lestari Manggong; Amaliatun Saleha (Jurnal Lingua Idea, 2021)
Released in May 2018, the song “Anpanman” by the world’s most popular K-Pop boy group to date, BTS, shares the idea of being a hero by setting an example from the Japanese superhero Anpanman. Anpanman, whose head is made of red bean paste-filled pastry, is well-known for his superpower ability to share parts of his head to those in need. This humble and self-sacrifice mode of helping others seems to be the basic idea of the song, to represent what BTS is about. This essay aims to further dissect the song lyrics of “Anpanman” to show the ambivalence presented between the concept of hero and superhero (termed here as (super)hero). The discussion goes further to juxtaposing the concept of hero/superhero with idol, a term used as another one of BTS’s songs “Idol”. Considering that in K-Pop, being an idol is practically a dream job, it is therefore paramount that in discussing the songs, this essay highlights the paradox of what it means to be a hero/superhero with an idol. Within the frame of network analysis, the discussion is conducted specifically along the line of the effects that digital culture has, which helps the spreading of BTS’s popularity and persona globally. In this light, this essay argues that beyond the songs, a problematic view on what it means to be a hero and an idol is projected. Ultimately, the discussion concludes that such an ambivalent view potentially leads to a reconceptualization of a superhero figure.Released in May 2018, the song “Anpanman” by the world’s most popular K-Pop boy group to date, BTS, shares the idea of being a hero by setting an example from the Japanese superhero Anpanman. Anpanman, whose head is made of red bean paste-filled pastry, is well-known for his superpower ability to share parts of his head to those in need. This humble and self-sacrifice mode of helping others seems to be the basic idea of the song, to represent what BTS is about. This essay aims to further dissect the song lyrics of “Anpanman” to show the ambivalence presented between the concept of hero and superhero (termed here as (super)hero). The discussion goes further to juxtaposing the concept of hero/superhero with idol, a term used as another one of BTS’s songs “Idol”. Considering that in K-Pop, being an idol is practically a dream job, it is therefore paramount that in discussing the songs, this essay highlights the paradox of what it means to be a hero/superhero with an idol. Within the frame of network analysis, the discussion is conducted specifically along the line of the effects that digital culture has, which helps the spreading of BTS’s popularity and persona globally. In this light, this essay argues that beyond the songs, a problematic view on what it means to be a hero and an idol is projected. Ultimately, the discussion concludes that such an ambivalent view potentially leads to a reconceptualization of a superhero figure.